2008
DOI: 10.1021/jp8006969
|View full text |Cite
|
Sign up to set email alerts
|

Template-Free Synthesis of Uniform CdS Hollow Nanospheres and Their Photocatalytic Activities

Abstract: A simple and facile template-free method has been developed for the fabrication of CdS hollow nanospheres via hydrothermal treatment of aqueous solutions of cadmium acetate and thiourea. Based on the detailed investigation on the influences of experimental parameters including the precursor chemical concentrations, reaction time, and reaction temperature, the formation mechanism of the hollow interiors by an Ostwald ripening process was the first time proposed for CdS hollow nanospheres. In particular, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(102 citation statements)
references
References 85 publications
4
98
0
Order By: Relevance
“…Thus, we propose that thiourea plays two important roles in the formation of ZnS nanospheres: It acts as a complexing reagent by forming Zn 2 + -thiourea ligands and as the source of sulfur after breaking of the C=S double bond by the strong nucleophilic substitution of the oxygen atoms of H 2 O molecules. [33] The probable reaction processes for the formation of ZnS nanospheres can be summarized by Equations (2)-(4).…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Thus, we propose that thiourea plays two important roles in the formation of ZnS nanospheres: It acts as a complexing reagent by forming Zn 2 + -thiourea ligands and as the source of sulfur after breaking of the C=S double bond by the strong nucleophilic substitution of the oxygen atoms of H 2 O molecules. [33] The probable reaction processes for the formation of ZnS nanospheres can be summarized by Equations (2)-(4).…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[34][35][36][37][38][39]. The results also showed that the degree of degradation was enhanced in lower pH medium.…”
Section: Effect Of Medium Ph On Mb Degradationmentioning
confidence: 81%
“…Lin et al developed a template-free method for the fabrication of CdS hollow nanospheres. [12] The obtained hollow nanosphere catalyst demonstrated good photocatalytic activity for methylene blue degradation. However, most of the hollow nanostructured catalysts are for metal particles or their derivatives.…”
Section: Introductionmentioning
confidence: 92%